Evaluation and Comparison the Antibacterial Activity of Silver Nano Particles (AgNPs) and Silver Nitrate (AgNO3) on Some Pathogenic Bacteria - Halah Dawood Salman (Journal of Global Pharma Technology, 2017)
Resistance of bacteria to some antibiotics increased tremendously therefore demanding for solutions and new medicine becomes essential as this problem related to human health. For this purpose, using of nanoparticles increased rapidly during the last years. In this study, the effect of silver nanoparticles (AgNPs) and silver nitrate (AgNO3) on bacteria had been evaluated and compared. Commercial purchased silver nanoparticles (with the particles size 20nm and Scanning Electron Microscopy (SEM) image) were characterized by X-ray diffraction (XRD). Antimicrobial activity of nanoparticles Silver and silver nitrate were evaluated on some pathogenic bacteria including samples including: Streptococcus pyogenes and Staphylococcus aureus (Gram Positive Bacteria)and Escherichia coli , Klebsiella pneumonia, Salmonella typhi, Acine to bacter baumannii and Vibrio cholerae (Gram Negative Bacteria).In this research, antibacterial activity for nanoparticle silver and silver nitrate at different concentrations started from 10 to 150μg ml−1against bacterial isolates was measured by agar diffusion technique and Minimum Inhibitory Concentration (MIC)/ Minimum bactericidal Concentration (MBC).These pathogens caused different hazardous infections and some of these bacteria are multi-drug resistant, the results exhibited remarkable antibacterial activity of silver nanoparticles (AgNPs) compared to moderate effect of silver nitrate (AgNo3) against most tested isolates including serious Gram Negative Bacteria resistant bacteria K.pneumonia , S. typhi and V. cholerae , the exception was A. baumannii as these bacteria didn’t affected definitely by any concentrations of Ag NPs or AgNo3 in the detection tests of MIC and MBC. Keywords: Silver Nan particles, Silver Nitrate, Pathogenic Bacteria